Primary Amenorrhea: A Müllerian Agenesis Case Report - Blake R. Busey; Rebecca J. Caro; Dana R. Nguyen (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
A case of müllerian agenesis, Mayer-Rokitansky-Küster-Hauser (MRKH) Syndrome, in a 16 year-old female with primary amenorrhea is reported. This patient exhibited normal female external physical characteristics with a shallow, blind vaginal pouch upon examination. Serologic hormone evaluation as well as karyotype determination revealed normal pubertal female range hormones and 46, XX, respectively. MRKH Syndrome has a prevalence of 1 in 4000 to 10000 females. Treatment is multi-factorial and should include nonsurgical vaginal dilator therapy, surgical neovaginal options, as well as psychosocial support and counseling on future reproductive options.